Applying Malaysia government website guidelines onto Ministry of Plantation Industries and Commodities (MPIC) website / Rafidah Mohd Ramli - Mohd Ramli, Rafidah Mohd Ramli (2016)
Every year United Nations Public Administration Network (UNPAN) presents the state of E-Government Development Index (EGDI) of the United Nation (UN)countries. Malaysia as a UN country since 1957, were also included in the index. EGDI design to capture e-government development along with an assessment of the e-government website. Malaysia e-government portal or my Government (myGov) are part of the assessments index. Therefore, all website listed in the myGov Portal were also evaluate by UNPAN. In order to achieve excellent index, Malaysian Administrative Modernization and Management Planning Unit (MAMPU) are responsible to report the achievement and performance of government agencies portal and website through an assessment program known as Portals Provider-Base Evaluation (ProBE). MAMPU has circulated the ProBE Guideline to all government agencies to be obliged and applied to the portal and website of the respective agency. Therefore, it has been an interest of this study to develop a prototype website to test either the ProBE guidelines are complied before the real assessment begin. The result of this study are shows from 47 criteria of the guidelines, the prototype has complied45 criteria, findings onto the implementation of ProBE guideline towards the prototype website before moving to the production server. Research was done through observations, interviews, focus group session, formal meetings, documents review and prototyping development. This study significantly helps MPIC development team to deliver a ProBE compliance website to the stakeholders and citizens. It is hope in the future; this research will help others to study on the effectiveness of implementing ProBE guideline in government website.